Pelatihan Komunikasi Pelayanan Costumer Experience (CX) Pada Komunitas Kedai Kopi Bekasi Timur Untuk Meningkatankan Kepuasan Pelanggan - Prasojo, Prasojo; Arifianto, M Lukman; Irfansyah, Azhar (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2024)
The Covid pandemic has changed customer service expectations for coffee shop managers. Customers expect service adaptations based on post-pandemic situations and conditions so that their needs continue to be met. Not all coffee shop managers can immediately adapt to customer desires, so they need to get assistance to be able to adapt to customer demands. Currently the situation has begun to shift from a pandemic to an endemic, of course customer expectations have also changed again. Therefore, this community service activity with an entrepreneurial scheme has a moment of urgency to provide a solution to the problem of adapting coffee shop managers to customer expectations. In general, the community service activities for the entrepreneurship scheme are focused on increasing the management capacity and capability of partner coffee shop entrepreneurs in East Bekasi through a customer survey process. At a further stage, this community service activity will carry out a series of training and assistance to adapt management and standard operational procedures (SOP) for coffee shop management to suit customer expectations. The survey results will be tabulated and analyzed as material for adapting management and management SOPs to suit customer expectations